Visible-light-driven hydrogen production from water in a noble-metal-free system catalyzed by zinc porphyrin sensitized MoS2/ZnO. (December 2015) - Yuan, Yong-Jun; Tu, Ji-Ren; Ye, Zhi-Jun; Lu, Hong-Wei; Ji, Zhen-Guo; Hu, Bin; Li, Yong-Hui; Cao, Da-Peng; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract: Photocatalytic hydrogen production system using zinc oxide as a photocatalyst typically suffer from low efficiency because of the wide band gap of ZnO. Despite tremendous efforts, it is still a great challenge to design efficient visible-light-responsive ZnO-based photocatalysts for hydrogen production. Herein, a new system for visible-light-driven hydrogen evolution was constructed by using Zn(II)-5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin dye-sensitized MoS2 /ZnO as a photocatalyst and triethanolamine as the sacrificial reductant. Even without any noble metal, the as-prepared composite photocatalyst loaded with 0.50 wt% MoS2 has a H2 production rate of 75 μmol h −1 g −1 under visible light irradiation ( λ > 420 nm), and the turnover number with respect to zinc dye reaches 516 after 9 h visible light irradiation. This study might offer a new paradigm for constructing efficient, visible-light-responsive and noble-metal-free solar-to-H2 conversion system by using dye-sensitized semiconductor as the photocatalyst. Graphical abstract: Highlights: Zinc porphyrin dye for photocatalytic hydrogen production. Dye sensitized photocatalytic hydrogen evolution. Synthesis of low-cost, visible-light-responsive dye-sensitized photocatalyst. Noble-metal-free photocatalytic hydrogen production system.